Assessment of Health-related Quality of Life among Diabetic Out patients at Warangal Region Telangana India- A Cross-sectional Study - Wajid, Syed (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The effect of glycemic control on overall health-related quality of life (HRQoL) in patients with diabetes has not been explored in the Telangana state of India. Therefore, this study aimed to assess the HRQoL among diabetic patients in the Warangal region of Telangana. Methods: A prospective interview-based study was conducted among diabetic outpatients of the endocrinology department in the Warangal region of Telangana between July 2019 and March 2020. The HRQoL of the patients was assessed using the quality of life instrument for indian diabetes patients. Data were analyzed by IBM Statistical Package for Social Science (SPSS) Statistics 26 (IBM Inc., Chicago, IL, USA). Results: Out of 402 diabetic patients more males 259 (64.4%), than females were observed 143 (35.6%). Their mean age was 52.39 Â± (SD, 11.01). About 26.1% of the patients (n = 105) had good physical HRQoL, while 38.3%(n = 154) reported poor general health. The domains such as diet and treatment satisfaction were found to have 30.8% (n = 124), 33.1% (n = 133) good HRQoL. The HRQoL toward emotional/mental health was reported poorly, only 15.7% (n = 63) of them were found to have good HRQoL. Conclusion: The findings indicated that patients in this study had relatively poor HRQoL associated with diabetes. The QoL has impaired mainly general, emotional health, also the domain of symptoms botherness. Therefore, better management of diabetes is needed for improved quality of life of patients through patient education.